2021
DOI: 10.1038/s41467-021-26415-4
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of Tremelimumab with and without cryoablation in patients with metastatic renal cell carcinoma

Abstract: Cryoablation in combination with immune checkpoint therapy was previously reported to improve anti-tumor immune responses in pre-clinical studies. Here we report a pilot study of anti-CTLA-4 (tremelimumab) with (n = 15) or without (n = 14) cryoablation in patients with metastatic renal cell carcinoma (NCT02626130), 18 patients with clear cell and 11 patients with non-clear cell histologies. The primary endpoint is safety, secondary endpoints include objective response rate, progression-free survival, and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…With the development of ICIs targeting CTLA-4 and PD-1 to enhance antitumour T cell activity, these immunotherapies are the current first-line treatments [ 7 , 28 , 29 ]. Based on a knowledge of the relative impacts of the treatments on both the cancer itself and the tumour microenvironment, combination therapies are also now being explored involving single-agent TKIs and ICIs [ 7 , 29 ] and more recently a pilot study of anti-CTLA-4 (tremelimumab) in combination with CRYO, which showed a significant increase in CD3+ and CD8+ T cell infiltration) in the tumour microenvironment compared with tremelimumab monotherapy [ 31 ]. Interestingly, these effects were restricted to the clear cell RCC histological subtype.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of ICIs targeting CTLA-4 and PD-1 to enhance antitumour T cell activity, these immunotherapies are the current first-line treatments [ 7 , 28 , 29 ]. Based on a knowledge of the relative impacts of the treatments on both the cancer itself and the tumour microenvironment, combination therapies are also now being explored involving single-agent TKIs and ICIs [ 7 , 29 ] and more recently a pilot study of anti-CTLA-4 (tremelimumab) in combination with CRYO, which showed a significant increase in CD3+ and CD8+ T cell infiltration) in the tumour microenvironment compared with tremelimumab monotherapy [ 31 ]. Interestingly, these effects were restricted to the clear cell RCC histological subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Shao qi et al have demonstrated that cryoablation (−80 °C, 30 min) on B16 cancer cells resulted in an 8.25 times release of natural proteins and activated a stronger T-cell immune response, which is 1.6 times more than the heating treatment group (50 °C, 30 min) [ 112 ]. Combining cryoablation, IFN- and VEGF signaling pathways are activated and further enhanced, providing a good induction pathway for immune cell infiltration in the tumor microenvironment [ 113 ]. In addition to the ability to increase the killing activity of immune cells such as T cells and NK cells, the underlying mechanism may contribute to the modulation of immune responses by promoting a release of Hsp70 and reducing Ki67 activity [ 114 , 115 , 116 ].…”
Section: Cancer Treatments Combined With Thermal Therapymentioning
confidence: 99%
“…Recently, Campbell, M.T. et al conducted a preliminary study using Tremelimumab immunotherapy with and without cryoablation in 29 patients with metastatic renal cell carcinoma [ 113 ]. They found a significant increase in T-cell infiltration in the tumor microenvironment of patients after cryo-trimethoprim combination therapy and laid an important foundation for subsequent combination therapy for patients with mccRCC.…”
Section: Cancer Treatments Combined With Thermal Therapymentioning
confidence: 99%
“…There are compelling preclinical and early clinical data to suggest that interventions such as thermal ablation and transarterial embolization can augment local and systemic tumor immunity [ 26 , 27 , 28 , 298 , 299 , 300 , 301 , 302 , 303 , 304 ]. The thermal ablation modalities such as radiofrequency ablation and microwave ablation cause the destruction of the tumor cells by causing necrosis, whereas cryoablation cause tumor destruction via both necrosis and apoptosis.…”
Section: Applications In Interventional Oncologymentioning
confidence: 99%